Carboxylic-functionalized water soluble pi-conjugated polymer: highly selective and efficient chemosensor for mercury(II) ions - Balamurugan, A.; Reddy, M. L. P.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Here, we report a new carboxylic-functionalized water soluble pi-conjugated polymer for selective detection of highly toxic Hg(2+) in neutral pH condition. carboxylic-functionalized thiophene containing oligophenylenevinylene was synthesized and polymerized under oxidative route to obtain water soluble polymer. Free carboxylic groups present in the pi-conjugated materials provide opportunity to use pH as external stimuli for studying secondary interaction such as hydrogen bonding and aromatic pi-stacking of the chromophores. The pH changes strongly influence on the molecular interactions in the monomer, whereas the long chain polymer was less disturbed. The polymer showed high selectivity for detecting Hg(2+) ions compared with any other transition metal ions in water. The detection efficiency of the polymer was found almost 40 times higher than that of its monomeric unit. Stern-Volmer constant for the Hg(2+) ion sensing was determined through concentration dependent studies as 6.4 x 10(5) M(-1). The carboxylic-functionalized polymer showed reversibility in the metal-ion detecting capabilities which was further investigated by NaCl complexation with Hg(2+) complex. Both funneling of excitation energy to the Hg(2+) center and also excitation energy migration through chain pi-conjugated backbone were correlated to the superior sensing characteristics of the polymer compared to its monomeric counterpart. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 5144-5157, 2009
Keywords: conjugated polymer; pH sensitive; photophysical studies; sensing; synthesis; water soluble

Comparing ultraviolet and chemical reduction techniques for enhancing photocatalytic activity of silver oxide/silver deposited nanocrystalline anatase titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K.; Warrier, K. G. K. (Journal of Physical Chemistry C, 2009)
Silver oxide/silver have been deposited, with varying silver concentration (0.01-10 mol %), on the surface of sol-gel derived nanocrystal line anatase titania using two different techniques, namely the ultraviolet reduction and chemical reduction (using stannous ions). The pure and silver oxide/silver-deposited nanocrystalline anatase titania have been characterized for their morphology, average nanocrystal lite size, specific surface area, phases involved, surface chemistry, band gap, and photoluminescence using various analytical techniques, such as scanning electron microscopy, transmission electron microscopy, Brunauer, Emmett, and Teller surface-area measurement, X-ray diffraction, X-ray photoelectron spectroscopy, ultraviolet-visible spectrophotometry, and spectrofluorometry, respectively. The photocatalytic activity of pure and silver oxide/silver-deposited nanocrystalline anatase titania has been measured by monitoring the degradation of methylene blue dye in an aqueous solution under ultraviolet-radiation exposure. Within the investigated Ag-concentration range, the maximum photocatalytic activity has been observed for 0.1 and 10 mol % Ag for the chemical-reduction (using stannous ions) and ultraviolet-reduction methods with the corresponding apparent first-order reaction-rate constant (k(app)) values of 0.228 and 0.151 min(-1), which are 3.5 and 2.3 times larger than that of pure nanocrystalline anatase fitania (0.065 min(-1)). The chemical-reduction method (using stannous ions), hence, appears to be more effective than the ultraviolet-reduction method for enhancing the photocatalytic activity of nanocrystalline anatase titania. Various factors such as the surface concentration of superoxide ions, oxygen-ion vacancies, and stannous ions as well as the amount of silver oxide/silver and tin oxide are observed to control the surface-adsorption of methylene blue and photoinduced electron/hole lifetime and, hence, variation in the photocatalytic activity as a function of silver concentration.

Enhanced solar-radiation induced photocatalytic activity of surface-modified nanocrystalline anatase-titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K. R.; Warrier, K. G. K. (Catalysis Letters, 2009)
Sol-gel derived pure nanocrystalline (similar to 20-30 nm) anatase-titania has been surface-modified by depositing silver(I) oxide and silver (predominantly the former) via UV-reduction process. The pure and surface-modified nanocrystalline anatase-titania have been characterized using different analytical techniques for determining the average nanocrystallite size, phase-contents, surface-chemistry, as well as the absorption and photoluminescence characteristics. It is demonstrated that, the latter exhibits an enhanced solar-radiation induced photocatalytic activity as compared to that of the former as a result of the absorption in the visible-region and enhanced photo-induced e(-)/h(+) life-time, both caused by the surface-deposition of silver(I) oxide and silver.
Keywords: Nanocrystalline; Photocatalysis; Silver; sol-gel; titania; UV-reduction